Is There an Interplay Between the Functional Domains of IRAP? - Vear, Anika; Gaspari, Tracey; Thompson, Philip; Chai, Siew Yeen (Frontiers in Cell and Developmental Biology, 2020)
As a member of the M1 family of aminopeptidases, insulin regulated aminopeptidase (IRAP) is characterised by distinct binding motifs at the active site in the C-terminal domain that mediate the catalysis of peptide substrates. However, what makes IRAP unique in this family of enzymes is that it also possesses trafficking motifs at the N-terminal domain which regulate the movement of IRAP within different intracellular compartments. Research on the role of IRAP has focussed predominantly on the C-terminus catalytic domain in different physiological and pathophysiological states ranging from pregnancy to memory loss. Many of these studies have utilised IRAP inhibitors, that bind competitively to the active site of IRAP, to explore the functional significance of its catalytic activity. However, it is unknown whether these inhibitors are able to access intracellular sites where IRAP is predominantly located in a basal state as the enzyme may need to be at the cell surface for the inhibitors to mediate their effects. This property of IRAP has often been overlooked. Interestingly, in some pathophysiological states, IRAP redistributes to the plasma membrane. This, together with the fact that IRAP possesses trafficking motifs, suggest the localisation of IRAP may play an important role in defining its physiological or pathological functions and provide insights into the interplay between the two functional domains of the protein.